member

JP2025036318APending Publication Date: 2025-03-14TOTO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024147017
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-08-28
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、防汚性に優れる表面を具備する部材、防汚性に優れる表面を被塗物上に効率よく形成することができる組成物、および前記部材の製造方法を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036318000001_ABST
    Figure 2025036318000001_ABST
Patent Text Reader

Abstract

To provide a member that can suppress adhesion of micro-scale or smaller contaminants such as proteins.SOLUTION: The present invention provides a member having a surface comprising a betaine structure, wherein, in observation using SEM-EDX, the number density of aggregates having an equivalent circle diameter of 4 μm or more is 100 / 1 mm2 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a member having a coating layer on its surface which is excellent in adhesion, hydrophilicity and antifouling properties, a composition capable of efficiently forming the coating layer on a substrate, and a method for producing the member. [Background technology]

[0002] In order to easily and inexpensively produce a member having a hydrophilic coating layer on its surface, a composition and a production method that allows hydrophilic groups to be unevenly distributed on the surface at a high concentration during film formation can be preferably used.

[0003] For example, WO2015 / 087810 (Patent Document 1) discloses that a cured product having hydrophilic groups segregated to the surface can be produced in a simple manner by polymerizing a composition that contains a specific surfactant in addition to a compound having a specific hydrophilic group and a functional group having a polymerizable carbon-carbon double bond, and a compound having two or more (meth)acryloyl groups.

[0004] In addition, WO2018 / 155577 (Patent Document 2) discloses that a surface containing a betaine structure exhibits high hydrophilicity, antifouling properties, and antifogging properties. In particular, it is known that a surface containing a betaine structure has an effect of suppressing protein adhesion (for example, JP-A-10-152533 (Patent Document 3)). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO2015 / 087810 publication [Patent Document 2] WO2018 / 155577 publication [Patent Document 3] Japanese Patent Application Publication No. 10-152533 Summary of the Invention [Problem to be solved by the invention]

[0006] The present inventors have now discovered a new problem in that a cured product produced by polymerizing a composition containing a compound having a betaine structure and a functional group having a polymerizable carbon-carbon double bond, and a compound having two or more (meth)acryloyl groups, as well as a specific surfactant, may not exhibit sufficient antifouling properties.

[0007] As a result of research aimed at solving the above problems, it was determined that the cause of insufficient antifouling properties was the occurrence of aggregation of components containing betaine structures on the surface of the coating layer, which resulted in the components being unevenly distributed on the surface. Components containing betaine structures are concentrated in the aggregated areas, and the amount of components containing betaine structures is reduced in non-aggregated areas, which makes it easier for contaminants of a size of micrometers or less, such as proteins, to adhere to the coating.

[0008] Therefore, it was found that by disposing the components containing the betaine structure uniformly on the surface of a component without causing aggregation of the components containing the betaine structure, it is possible to effectively prevent contamination by contaminants such as proteins that are smaller than a micrometer in size.

[0009] Furthermore, the inventors have found that by polymerizing a composition containing a compound having a betaine structure and a polymerizable functional group in its molecule, a compound characterized by having two or more polymerizable functional groups in its molecule, and a surfactant that dissolves in 2-methoxyethanol at a weight concentration of 0.1% or more and has 9 or more carbon atoms in the hydrophobic part of its molecule or has a polymerizable functional group in its molecule, it is possible to efficiently form a component in which the component containing the betaine structure is uniformly arranged on the surface without aggregation of the component containing the betaine structure.

[0010] The present invention is based on the above findings, and aims to provide a member having a coating layer with excellent antifouling properties on its surface, a composition capable of efficiently forming the coating layer with excellent antifouling properties on a substrate, and a method for manufacturing the member. [Means for solving the problem]

[0011] The member according to the present invention includes a substrate and a coating layer, The surface of the coating layer has the following formula (A1): [ka] The aggregates with a circle equivalent diameter of 4 μm or more, including the structure represented by 2 Contains 100 or less per In formula (A1), L1 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R1 is H or CH3; X1 is a functional group represented by the following formula (B1) or the following formula (B2), [ka] [ka] In formula (B1), R3 and R6 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R4 and R5 are each independently an organic group that contains C and H as essential components and O as an optional component, but does not contain N or S; In formula (B2), R7 and R8 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R9, R 10 , R 11 are each independently an organic group containing C and H as essential components and O as an optional component, and not containing N or S. It is characterized by: Effect of the Invention

[0012] According to the present invention, it is possible to provide a member having a surface with excellent antifouling properties, a composition capable of efficiently forming a surface with excellent antifouling properties on a substrate, and a method for producing said member. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic cross-sectional view of an example of a member according to the present invention. [Diagram 2] 13 is an image of the S element distribution on the surface of the coating layer of the component sample of Example 3 after the closing treatment. [Diagram 3] 13 is an image of the S element distribution on the surface of the coating layer of the component sample of Comparative Example 2 after the closing treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Materials The member according to the present invention (hereinafter, sometimes simply referred to as "member") includes a substrate and a coating layer, The surface of the coating layer has the following formula (A1): [ka] The aggregates with a circle equivalent diameter of 4 μm or more, including the structure represented by 2 Contains 100 or less per In formula (A1), L1 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R1 is H or CH3; X1 is a functional group represented by the following formula (B1) or the following formula (B2), [ka] [ka] In formula (B1), R3 and R6 each independently represent -(CH2) l- (l is a natural number from 1 to 10), R4 and R5 are each independently an organic group that contains C and H as essential components and O as an optional component, but does not contain N or S; In formula (B2), R7 and R8 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R9, R 10 , R 11 are each independently an organic group containing C and H as essential components and O as an optional component, and not containing N or S. It is characterized by:

[0015] FIG. 1 is a schematic cross-sectional view of an example of a member according to the present invention. In the embodiment shown in FIG. 1, the member 10 includes a substrate 1. The member 10 further includes a coating layer 2. The coating layer 2 is preferably on the outermost surface of the member 10. The member 10 may further include a primer layer 3. The member 10 may further include layers (not shown) other than those described above, as long as the effects of the present invention can be achieved. Whether the member 10 includes the coating layer 2 can be confirmed by observing a cross section of the member 10 using an electron microscope and separating the layers.

[0016] Coating layer In the present invention, the coating layer contains a structure represented by the following formula (A1). [ka]

[0017] In formula (A1), L1 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R1 is H or CH3; X1 is a functional group represented by the following formula (B1) or the following formula (B2), [ka] [ka] In formula (B1), R3 and R6 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R4 and R5 are each independently an organic group that contains C and H as essential components and O as an optional component, but does not contain N or S; In formula (B2), R7 and R8 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R9, R 10 , R 11 are each independently an organic group containing C and H as essential components and O as an optional component, and not containing N or S.

[0018] In the present invention, the coating layer may optionally contain a structure represented by the following formula (A2). [ka] In formula (A2), L2 is -COO-, -CONH-, -(CH2) m -(m is a natural number), -Ph- (phenyl group), R2 is H or CH3; X2 preferably contains any structure selected from the group consisting of the following formula (C), the following formula (F1), the following formula (F2), and the following formula (G). [ka] In formula (C), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; a is a natural number, R 12 includes any structure selected from the group consisting of H, CH3, C2H5, and the following formula (D1), the following formula (D2), the following formula (D3), and the following formula (D4). [ka] [ka] [ka] [ka]

[0019] In formula (D1), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3.

[0020] In formula (D2), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; X3 is a structure represented by the following formula (E1). [ka] In formula (E1), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; a is a natural number.

[0021] In formula (D3), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; X3 is a structure represented by the above formula (E1).

[0022] In formula (D4), X4 is a structure represented by the following formula (E2). [ka] In formula (E2), Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; a is a natural number. [ka] [ka] In formula (F2), R 13 is an organic group containing C and H as essential components, O as an optional component, and containing no N or S. [ka] In formula (G), R 14 is -(CH2) l - (l is a natural number from 1 to 10), R 15 , R 16 , R 17 are each independently an organic group containing C and H as essential components and O as an optional component, and containing no N or S.

[0023] By including a structure represented by formula (A1) on the surface of the coating layer, the member according to the present invention can have high hydrophilicity, and therefore has excellent antifogging and antifouling properties. In particular, it is possible to inhibit adhesion of various contaminants to the surface. In particular, it is possible to inhibit adhesion of proteins. The structure represented by formula (A1) is a betaine structure, as described below, and has antifouling ability (ability to inhibit adsorption of proteins). This performance makes it possible to inhibit adhesion of proteins to the surface of the member. In addition, by including a structure represented by formula (A2) on the surface of the coating layer, it is possible to further improve antifouling properties.

[0024] In the present invention, the surface of the coating layer is preferably a polymer layer. The polymer layer is a layer containing a polymer compound. In the present invention, the surface of the coating layer preferably contains a polymer compound containing a structure represented by formula (A1). It is more preferable that the surface of the coating layer contains a polymer compound containing a structure represented by formula (A1) and a structure represented by formula (A2). It is even more preferable that the surface of the coating layer contains a polymer compound containing only a structure represented by formula (A1) and a structure represented by formula (A2). In this case, it is preferable that the structure represented by formula (A1) and the structure represented by formula (A2) are randomly bonded.

[0025] The structure represented by formula (A1) and the structure represented by formula (A2) will be further explained.

[0026] A structure represented by formula (A1) In formula (A1), L1 is preferably -COO-. This makes it possible to further suppress adhesion of proteins or adhesion of water scale. When L1 is -CONH-, protein adhesion or water scale adhesion may occur starting from the N constituting -CONH-. In addition, when L1 is -(CH2) m If -, the hydrophobicity is increased and protein adhesion may occur.

[0027] In X1 in formula (A1), that is, in formula (B1) or formula (B2), l in R3, R6, R7, and R8 is preferably 1 to 6, more preferably 1 to 5, and even more preferably 1 to 3. This reduces the concentration of hydrophobic alkyl chains on the surface of the coating layer, and can improve hydrophilicity, antifogging properties, and antifouling properties.

[0028] In the present invention, the surface of the coating layer containing the structure represented by formula (A1) and optionally the structure represented by formula (A2) can be specified by any one of the following methods or a combination of multiple methods.

[0029] R4, R5, R9, R 10 , R 11 is preferably any one of an alkyl group, a hydroxyalkyl group, a carboxyalkyl group, a group represented by the following formula (L1), and a group represented by the following formula (L2). [ka] In formula (L1), p is a natural number. [ka] In formula (L2), q is a natural number. R4, R5, R9, R 10 , R 11 When the organic group is one of these, it is easy to synthesize a monomer that serves as a raw material for the structure of formula (B1) or formula (B2).

[0030] Also, R4, R5, R9, R 10 , R 11 is more preferably a methyl group. The monomers that are the raw materials of formula (B1) or formula (B2) are commercially available, and therefore are highly available. In addition, the concentration of organic groups, to which organic components such as proteins tend to adhere, in the surface layer can be reduced.

[0031] A structure represented by formula (A2) When X2 in formula (A2) is formula (F2), R13 is preferably a linear or branched chain hydrocarbon group having a carbon number of 1 to 6, preferably 1 to 5. This can reduce the concentration of alkyl chains in the surface layer to which organic components such as proteins tend to adhere, thereby improving the effect of inhibiting adhesion of organic components such as proteins to the surface layer.

[0032] When X2 in formula (A2) is formula (G), R 15 , R 16 , R 17 is preferably a methyl group, an ethyl group, or a benzyl group. These organic groups are easily available because the monomers that are the raw materials for the structure of formula (G) are commercially available. In addition, the concentration of organic groups to which organic components such as proteins tend to adhere can be reduced in the surface layer.

[0033] <Infrared spectroscopy (IR)> By measuring the infrared light absorption spectrum near the surface of the coating layer using infrared spectroscopy, it is possible to estimate the functional groups contained in the surface vicinity of the coating layer. For example, it is possible to identify the presence of -C=O and -CO- in an ester bond (-COO-) from the absorption wave number. Methods for measuring the infrared absorption spectrum near the surface of the coating layer include a method in which the surface vicinity of the coating layer is scraped off and the powder is collected and measured using a transmission method, and more convenient methods include a single reflection ATR method and a microscopic ATR method.

[0034] <Time-of-flight secondary ion mass spectrometry (TOF-SIMS)> TOF-SIMS can be used to obtain structural information on the organic substances present on the surface of the coating layer. By evaluating the surface of the coating layer with TOF-SIMS, it is possible to identify substructures from the fragment peaks specific to the structure represented by formula (A1) or the structure represented by formula (A2). For example, when the structure represented by formula (A1) is the structure represented by the following formula (A1-1), fragment peaks specific to m / z = 279.11 and m / z = 421.26 can be detected. Also, when the structure represented by formula (A2) is the structure represented by the following formula (A2-1), a fragment peak specific to m / z = 79.96 can be detected. When measuring with TOF-SIMS, as a pretreatment to remove dirt on the surface of the sample to be measured, the surface of the sample is sputtered by several nanometers using an ion source such as a gas cluster ion beam (GCIB), and then irradiated with a primary ion source such as Bi3 2+ and the like, and its fragments are measured.

Chemical formula

Chemical formula

[0035] <X-ray photoelectron spectroscopy (XPS)> By XPS under the XPS measurement conditions described later, it is possible to identify the composition ratio and chemical bond state of C, N, O, S, P, and Si contained in the molecules constituting the surface of the coating layer. For example, the XPS spectrum (N1s orbital) of N atoms derived from a sulfobetaine structure as shown in formula (A1-1) has a peak position at a binding energy of 401.5 eV when no other ionic mixtures are present. In contrast, when the structure represented by formula (A1) is a structure as shown in the following formula (A3) (a structure containing a cationic ammonium moiety) or a mixture of formula (A3) and the above formula (A2-1) (a structure containing an anionic sulfonic acid moiety), the peak positions are 402.0 eV and 401.8 eV, respectively. In this way, it is possible to identify whether or not an N atom is derived from sulfobetaine based on the difference in peak position. Similarly, it is possible to identify whether S atoms are derived from sulfobetaine from the peak position. The XPS spectrum (S2p orbital) of S atoms derived from the structure shown in formula (A1-1) has a peak position at a binding energy of 166.2 eV, whereas the peak positions are 167.5 eV and 167.1 eV for the structure shown in formula (A2-1) (anionic sulfonic acid) or a mixture of formula (A3) and formula (A2-1). All of these peak positions are obtained by correcting with the peak position of the C1s orbital at 284.5 eV. [ka]

[0036] <Nuclear magnetic resonance measurement (NMR)> NMR can provide information on the bonding state of H, C, and N contained in the molecules that make up the surface of the coating layer, as well as on interactions with neighboring atoms, by comparing chemical shifts with a standard sample. This allows the molecular structure that makes up the surface of the coating layer to be identified in detail.

[0037] Static contact angle of coating layer In the present invention, the static contact angle of water to the surface of the coating layer is preferably as low as possible. Specifically, it is preferably 35° or less, more preferably 30° or less, and even more preferably 20° or less. This increases hydrophilicity, making it possible to prevent adhesion of various contaminants including proteins.

[0038] The static contact angle of water with respect to the surface of the coating layer is measured, for example, using the following device and software under the following measurement conditions. Equipment: DMo-702 (Kyowa Interface Science Co., Ltd.) Software: FAMAS integrated interface measurement / analysis system Version:7.3.0 Measurement method: Droplet method Droplet volume: 2.0μL Waiting time: 1000ms Analysis method: θ / 2 method

[0039] The proportion of the structure represented by formula (A1) (betaine structure) on the surface of the coating layer In the present invention, the proportion of the structure represented by formula (A1) (betaine structure) on the surface of the coating layer is determined by the N + N atoms belonging to (hereinafter referred to as "N + In the present invention, the concentration of N atoms obtained by XPS measurement of the surface of the member can be defined as + The concentration of N atoms is preferably 0.3% or more, and more preferably 0.4% or more. + The concentration of N atoms is preferably 5.5% or less, and from the viewpoint of preventing the adhesion of water scale, + The concentration of the atoms is preferably 1.6% or less.

[0040] When the surface of the coating layer contains a structure represented by formula (G), the N + The concentration of atoms is N from the structure represented by formula (A1). + The concentration of atoms and N from the structure represented by formula (G) +It becomes the total concentration of atoms. In such a case, the proportion of the structure (betaine structure) represented by formula (A1) can be defined by the concentration of S atoms, the concentration of P atoms, or the total of the concentration of S atoms and the concentration of P atoms.

[0041] In the present invention, the concentration of S atoms, the concentration of P atoms, or the total of the concentration of S atoms and the concentration of P atoms obtained by XPS measurement of the surface of the member is preferably 0.3% or more, and more preferably 0.4% or more. In the present invention, from the viewpoint that the surface layer has a clean surface, the concentration of S atoms, the concentration of P atoms, and the total of the concentration of S atoms and the concentration of P atoms are preferably 5.5% or less.

[0042] <XPS measurement> · Preparation of measurement sample A measurement sample can be a flat plate-shaped region cut from a member sample with an appropriate size. It is preferable to clean the surface of the measurement sample before measurement. For example, it is more preferable to clean the surface of the measurement sample using a neutral detergent and a sponge, then perform ultrasonic cleaning with ultrapure water, and then thoroughly rinse with ultrapure water. · XPS measurement device For the XPS measurement device, K-alpha (manufactured by ThermoFisher Scientific Co., Ltd.) can be used. · XPS measurement conditions X-ray conditions: Monochromatized AlKα ray, 72W - 12KV Photoelectron extraction angle: 90° Analysis area: 400μmφ Neutralization gun conditions: 200μA Ion gun conditions: 10mA (Survey) Time per step: 10ms Energy step size: 1.000eV Sweep: 2 times Pass energy: 200eV Scanning range: -10~1350eV (Narrow) Time per step: 50ms Energy step size: 0.100 eV Sweep: 5 times Pass energy: 50 eV Scanning range: C1s peak 279.000 eV - 298.000 eV, O1s peak 525.000 eV - 545.000 eV, N1s peak 392.000 eV - 410.000 eV, S2p peak 157.000 eV - 175.000 eV, P2p peak 124.000 eV - 144.000 eV

[0043] <Calculation of atomic concentrations (S, N, P)> The atomic concentrations of the detected elements can be calculated from the obtained spectra using, for example, data analysis software Thermo Avantage (version 5.9916, manufactured by Thermo Fisher Scientific Co., Ltd.). First, use the spectra obtained from the survey analysis to confirm whether the cleaning has been properly performed. Then, perform charge correction on the spectra obtained from the narrow analysis with the C1s peak set at 284.5 eV. After that, remove the background by the Smart method for the peaks based on the electron orbits of each measured atom, calculate the peak area intensity, and perform an analysis process of dividing by the sensitivity coefficient specific to the device preset in the data analysis software to calculate the atomic concentrations when the total of C atoms, O atoms, N atoms, S atoms, and P atoms is 100%.

[0044] <Peak separation of N atoms> To separate the peak derived from the +1 valence N atom (N + ) contained in the betaine structure from the peak derived from other 0 valence N atoms (N 0 ), the following method can be used. Fix the peak position of N + at 401.4 - 401.8 eV and the full width at half maximum of the peak at 1.6 eV, fix the peak position of N 0 at 399.0 - 399.4 eV, and perform peak fitting. Calculate the atomic concentrations of N + , N 0 respectively from the results of the peak fitting.

[0045] The following conditions can be used for peak fitting. <Peak fitting conditions> Fitting Algorithm:Powell Maximum Iterations:90 Convergence:1e-05 Gauss-Lorentz Mix:Product

[0046] Observation of aggregation and calculation of the circle equivalent diameter of the aggregation In the coating layer of the present invention, the detection of aggregation of components including the structure represented by the formula (A1) and optionally the structure represented by the formula (A2) described later, and the calculation of the equivalent circle diameter of the aggregation can be performed by the following method.

[0047] By using a scanning electron microscope - energy dispersive X-ray spectroscopy (SEM-EDX), intensity mapping of elements present near the surface of the coating layer can be performed. The surface distribution of the structure represented by the formula (A1) and optionally the structure represented by the formula (A2) can be obtained by mapping the X-ray detection intensity distribution derived from S atoms or P atoms characteristic of each structure.

[0048] <SEM-EDX measurement> · Preparation of measurement sample A flat plate-shaped region cut from the member sample with an appropriate size can be used as the measurement sample. It is preferable to clean the surface of the measurement sample before measurement. For example, it is more preferable to clean the surface of the measurement sample using a neutral detergent and a sponge, and then thoroughly rinse it with ultrapure water. Also, conduct a conductivity treatment so that the distribution of the element to be analyzed can be appropriately analyzed. · SEM-EDX measurement device and measurement conditions For the SEM measurement device, Regulus8220 (Hitachi High-Tech Corporation) can be used, and for the EDX measurement device: XFlash5060FlatQUAD (Bruker Corporation), and the measurement can be performed under the following conditions. · SEM-EDX measurement conditions Acceleration voltage: 6 kV Irradiation current: 10μA Condenser lens 1:8 Magnification: 250x ·EDX analysis elements It is preferred to analyze S or P, which are characteristic elements of the structure of formula (A1) and optionally of the structure of formula (A2).

[0049] <Calculation and counting of the equivalent circle diameter of aggregates> The calculation and counting of the circular equivalent diameter of aggregates in the obtained element distribution image can be carried out using commercially available image analysis software or an image analysis library.

[0050] In the present invention, the determination of aggregation on the surface of the structure represented by formula (A1) and optionally the structure represented by formula (A2) of the coating layer, and the calculation and counting of the equivalent circle diameter of the aggregates can be performed by the following method. Loading an image: Load the obtained SEM-EDX image. The image size of the SEM-EDX image should be 960px vertical and 1280px horizontal. -Cutting out the analysis part: Cut out the display part of the analysis part, such as the scale bar and measurement conditions, so that they are not included in the analysis part. Monochrome processing: Converts the image to monochrome. Gaussian blurring: Set the kernel size to 3px vertically and 3px horizontally. · Binarization processing: The threshold is the 90th percentile value of the pixel values ​​of the entire image. Opening process: Opening process is performed to remove noise. The kernel size is set to 3px vertical and 3px horizontal. Closing: Performs closing to fill holes in the foreground area. The kernel size is set to 3px vertical and 3px horizontal. Extraction of connected regions: Extract connected regions and make them into aggregates. Calculation of the equivalent circle diameter: The area of ​​the aggregate ( S ) to the equivalent circle diameter ( R ) to calculate

number

[0051] The surface of the coating layer in the present invention has a number density of aggregates having an equivalent circle diameter of 4 μm or more, which include a structure represented by formula (A1) and, in some cases, a structure represented by formula (A2), of 100 aggregates / mm 2 The number density of the aggregates is 10 / mm 2 It is preferable that the number of particles is less than 1 / mm. 2 It is more preferable that:

[0052] Simple assessment of aggregation When components containing the structure represented by formula (A1) and, in some cases, the structure represented by formula (A2) are aggregated, an uneven structure of about several hundred nm to several μm is formed on the surface. Therefore, when the substrate is transparent, the presence or absence of aggregation on the surface of the coating layer can be determined by the haze value. When the haze value of a component is 7.0 or more, it can be determined that aggregation exists on the surface of the coating layer. However, determining aggregation by the haze value is a simple evaluation, and accurate evaluation requires detection of aggregates using the above-mentioned SEM-EDX and calculation of the circle equivalent diameter of the aggregates.

[0053] The haze value of a member is measured, for example, using the following device. Equipment: Hazeguard i (BYK-Chemie) Measurement item: Transmitted haze value

[0054] Coating layer thickness The thickness of the coating layer formed in the present invention is preferably in the range of 0.1 μm to 200 μm. This provides a sufficient effect of suppressing protein adhesion and also allows abrasion resistance to be exhibited. The thickness of the coating layer is preferably in the range of 1 to 100 μm, more preferably in the range of 1 to 20 μm.

[0055] The film thickness of the coating layer can be measured by cross-sectional observation using SEM or the like.

[0056] <Film thickness measurement by SEM> · SEM apparatus For the SEM apparatus, Regulus8220 (manufactured by Hitachi High-Tech Corporation) can be used and measurement can be performed under the following conditions. · SEM measurement conditions Acceleration voltage: 1 kV Magnification: 20,000 to 400 times

[0057] Concentration ratio between the surface and the interior of the structure represented by formula (A1) When the surface of the coating layer is defined as the film thickness depth 0 point and the interface between the coating layer and the base material is defined as the film thickness depth 1 point, the ratio (B / S) of the presence ratio (B) of the structure represented by formula (A1) at the film thickness depth 1 / 10 point to the presence ratio (S) of the structure represented by formula (A1) at the film thickness depth 0 point is preferably 0 or more and less than 1, more preferably 0 or more and less than 0.8, and even more preferably 0 or more and less than 0.6. That is, the coating layer preferably contains a large amount of the structure represented by formula (A1) on the surface side and is, for example, an inclined film containing a large amount of an acrylic resin or a polyvinyl resin in the main chain described later on the base material side. Thereby, while the surface of the member has high hydrophilicity, antifogging property, and antifouling property, it becomes possible to ensure adhesion to the base material. In addition, in the coating layer of the present invention, the concentration ratio of the structure represented by formula (A1) on the surface and inside thereof can be measured by the following method.

[0058] <Gas cluster ion beam - X-ray photoelectron spectroscopy (GCIB-XPS)> The coating layer is sputtered with Ar gas cluster ions, and the surface exposed at each specific sputtering time is measured by XPS, and N + By calculating the concentration of atoms, the depth distribution of the structure represented by formula (A1) can be measured. Further, from the depth distribution, the concentration ratio of the structure represented by formula (A1) on the surface and inside of the coating layer can be calculated.

[0059] <XPS Measurement> · Preparation of Measurement Sample A flat plate-shaped area cut from a member sample with an appropriate size can be used as the measurement sample. It is preferable to clean the surface of the measurement sample before measurement. For example, it is more preferable to clean the surface of the measurement sample using a neutral detergent and a sponge, then perform ultrasonic cleaning with ultrapure water, and finally thoroughly rinse with ultrapure water. · XPS Measurement Device As the XPS measurement device, QUANTERA II (manufactured by ULVAC-PHI, Inc.) can be used. · XPS Measurement Conditions X-ray Conditions: Monochromatized AlKα ray, 25W - 15KV Photoelectron Extraction Angle: 45° Analysis Area: 100μmφ Neutralizer Gun Conditions: Auto Neutralizer Ion Gun Conditions: Auto Neutralizer Time per step: 50ms Energy step size: 0.100eV Sweep: 5 times Pass energy: 55eV Scanning Range: C1s peak 279.000eV - 299.000eV, O1s peak 525.000eV - 545.000eV, N1s peak 392.000eV - 410.000eV, S2p peak 157.000eV - 177.000eV, P2p peak 124.000eV - 144.000eV · GCIB Sputtering Conditions The following conditions can be used for GCIB sputtering. Beam Voltage: 10kV Beam Current: 30nA

[0060] <Calculation of the Concentration of Each Atom (S, N, P)> The atomic concentration of the detected elements can be calculated from the obtained spectrum using, for example, data analysis software MultiPaK (version 9.0, manufactured by ULVAC-PHI, Inc.). For the spectrum obtained by narrow analysis, charge correction is performed with the C1s peak set at 284.5 eV. Thereafter, the background is removed from the peaks based on the electron orbits of the measured atoms by the Shirley method, and then the peak area intensity is calculated. An analysis process is performed in which the calculated value is divided by the sensitivity coefficient specific to the apparatus preset in the data analysis software, and the atomic concentration of each atom is calculated when the total of C atoms, O atoms, N atoms, S atoms, and P atoms is 100%.

[0061] <Separation of N atom peaks> For separating the peak derived from the +1 valence N atom (N + ) contained in the betaine structure from the peak derived from the other 0 valence N atom (N 0 ), the following method can be used. The peak position of N + is fixed at 401.4 to 401.8 eV, and the full width at half maximum of the peak is fixed at 1.6 eV. The peak position of N 0 is fixed at 399.0 to 399.4 eV, and peak fitting is performed. From the result of the peak fitting, the atomic concentration of each of N + and N 0 is calculated.

[0062] The following conditions can be used for peak fitting. <Peak fitting conditions> Fitting Algorithm: Powell Maximum Iterations: 90 Convergence: 1e-05 Gauss-Lorentz Mix: Product

[0063] When the coating layer contains a structure represented by formula (G), the concentration of N + atoms obtained by XPS measurement is the N + atom concentration derived from the structure represented by formula (A1) and the N derived from the structure represented by formula (G)+ In such a case, the abundance ratio of the structure represented by formula (A1) (betaine structure) can be determined by the concentration of S atoms, the concentration of P atoms, or the sum of the concentrations of S atoms and P atoms.

[0064] Surface properties of the component The member according to the present invention preferably has sufficient abrasion resistance so as to exert effects such as hydrophilicity, antifogging, and antifouling properties for a long period of time in various usage environments. For example, when used around water, the member is maintained by rubbing the member with a sponge or cloth soaked in water and a detergent containing water. The member according to the present invention preferably has a static contact angle of water on the coating layer of 35 degrees or less after the following sliding durability evaluation test is performed. This allows the member to have sufficient sliding durability and maintain the effects of hydrophilicity, antifogging, and antifouling properties for a long period of time even in the above-mentioned environment.

[0065] <Sliding durability evaluation> The member according to the present invention can be subjected to a sliding durability test using a sliding machine (manufactured by Tester Sangyo Co., Ltd.) according to the following method. A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) was soaked in a mixture of water and neutral detergent (Bath Magiclean, manufactured by Kao Corporation) in a weight ratio of 90:10, and subjected to a load of 25 [g / cm 2 ] is moved back and forth over the surface of the member 5000 times. After washing the member with running water, it is dried and the static contact angle of water is measured by the method described above.

[0066] <Protein adsorption amount> The protein adhesion inhibiting effect of the member according to the present invention can be indicated by the amount of protein adsorption obtained according to the procedure described below.

[0067] (Preparation of protein-containing suspension) To 100 mL of ion-exchanged water, 1.0 g of BSA (bovine serum albumin (FV), pH 5.2, Nacalai Tesque, Inc.) is added as a protein, and the mixture is mixed with a stirrer for 1 hour to obtain a suspension.

[0068] (Protein adhesion and cleaning) After immersing the component in the suspension for 5 minutes, the component is removed from the suspension. The component is then dried in a thermostatic chamber at 40°C for 10 minutes. Then, ultrapure water is applied to the surface of the component using a dropper at a concentration of 0.4 [mL / cm 2 This procedure is repeated three times to obtain a material with BSA attached.

[0069] <Protein recovery and sample solution preparation> Wipe off the BSA from the components with a nonwoven fabric. Place the nonwoven fabric from which the BSA has been wiped off into a 20mL headspace vial (As One Corporation), add 2mL of 6mol / L hydrochloric acid, and leave at 110°C for 20 hours to hydrolyze. Then, dry it on a hot plate at 120°C for 3 hours, add 2mL of ultrapure water to dissolve the amino acids, and use the component sample solution. Also, hydrolyze BSA that was previously weighed using the same procedure to use the calibration curve sample solution.

[0070] <High performance liquid chromatography (HPLC) measurement> HPLC measurement equipment Nexera Post-column Amino Acid Analysis System (Shimadzu Corporation) HPLC measurement conditions Column: Shim-pak amino-Na (Shimadzu Corporation) Ammonia trap column: ISC-30Na (Shimadzu Corporation) Mobile phase: Three-liquid gradient amino acid mobile phase kit Na type (Shimadzu Corporation) Flow rate: 0.6ml.min Reaction reagent: Amino acid analysis kit OPA reagent (Shimadzu Corporation) Flow rate: 0.2ml / min Detector: RF-10AXL (Shimadzu Corporation) Excitation wavelength 350 nm, emission wavelength 450 nm ·BSA quantitative method HPLC measurement is performed on the component sample solution and the calibration curve sample solution, and the sum of the peaks in the obtained chromatogram is regarded as the peak area value. The amount of BSA in the component sample solution is calculated based on the calibration curve created from the calibration curve sample. This amount of BSA is regarded as the amount of protein adsorbed on the component.

[0071] The protein adsorption amount of the member according to the present invention obtained as described above is 7.5 μg / cm 2 More preferably, it is 5.0 μg / cm 2 and even more preferably 1.0 μg / cm 2 The following is the result.

[0072] Coating layer forming composition In the present invention, the coating layer is preferably a composition obtained by curing a coating layer-forming composition. In the present invention, the coating layer-forming composition may be a hydrophilic composition including a compound having a betaine structure, a monomer capable of forming a polyacrylic or polyvinyl copolymer, a polymerization initiator, a surfactant that dissolves in 2-methoxyethanol at a weight concentration of 0.1% or more and has 9 or more carbon atoms in the hydrophobic part of the molecule or has a polymerizable functional group, and a solvent. In addition, the composition may include one or more types selected from nonionic monomers, anionic monomers, and cationic monomers as optional components.

[0073] Compounds with a betaine structure In the present invention, the composition for forming a coating layer can contain a compound having a betaine structure. This allows the coating layer obtained by curing the composition for forming a coating layer to contain a structure represented by formula (A1). In the present invention, a compound having a betaine structure means a compound having at least one or more cations, anions, and an ethylenically unsaturated group in the same molecule. In the present invention, examples of the cation include cations such as quaternary ammonium, sulfonium, and phosphonium. Examples of the anion include -COO - , -PO4 2-, -HPO4 - , -SO3 - Examples of anions include:

[0074] In the present invention, the compound having a betaine structure contains a quaternary ammonium as a cation in the molecule and -SO3 as an anion. - Sulfobetaine containing quaternary ammonium as the cation and -PO4 as the anion in the molecule 2- Among them, phosphobetaines containing quaternary ammonium as a cation and -SO3 as an anion in the molecule are preferred. - More preferred is a sulfobetaine containing the following: Further preferred is a sulfobetaine having a (meth)acrylic skeleton in the molecule.

[0075] In the present invention, an example of a compound having a betaine structure is compound 1 represented by the following formula (H1). Compound 1: [ka] In Compound 1, L1 includes any one of -COO-, -CONH-, and -(CH2)m- (m is a natural number); R1 is H or CH3; R3 and R6 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R4 and R5 are each independently an organic group that contains C and H as essential components and O as an optional component, and does not contain N or S. It is characterized by: Incidentally, it is possible to specify that L1 contains -COO- from the above-mentioned IR.

[0076] In the present invention, an example of a compound having a betaine structure is compound 2 represented by the following formula (H2). Compound 2: [ka] In compound 2, L1 includes any one of -COO-, -CONH-, and -(CH2)m- (m is a natural number); R1 is H or CH3; R7 and R8 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R9, R 10 , R 11 are each independently an organic group containing C and H as essential components and O as an optional component, and containing no N or S.

[0077] In the present invention, specific examples of compounds having a betaine structure include 3-[[2-(acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 4-[(3-methacrylamidopropyl)dimethylammonio]butane-1-sulfonic acid, 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl] phosphate, 4-[[2-(methacryloyloxy)ethyl]dimethylammonio]butane-1-sulfonic acid, 3-[(3-acrylamidopropyl)dimethylammonio]propane-1-sulfonic acid, and 3-[(3-methacrylamidopropyl)dimethylammonio]propane-1-sulfonic acid. Among these, 3-[[2-(acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, [3-(methacryloylamino)propyl]dimethyl(3-sulfobutyl)ammonium hydroxide, and 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl phosphate are preferred.

[0078] Compounds containing two or more polymerizable functional groups In the present invention, the composition for forming a coating layer may contain a compound having two or more polymerizable functional groups. Examples of the compound having two or more polymerizable functional groups include a monomer constituting a polyacrylic copolymer and a monomer constituting a polyvinyl copolymer.

[0079] <Multifunctional acrylate> As a monomer constituting the polyacrylic copolymer, a multifunctional acrylate can be suitably used. In the present invention, the multifunctional acrylate means a monomer having at least two or more ethylenically unsaturated groups in the molecule. Specific examples of the multifunctional acrylate include 2-hydroxy-3-acryloyloxypropyl methacrylate, propoxylated ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A diacrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, propoxylated bisphenol A diacrylate, tricyclodecane dimethanol diacrylate, 1,10-decane diol diacrylate, 1,6-hexanediol diacrylate, 1,9-nonane diol diacrylate, and the like. All diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, ethoxylated isocyanuric acid triacrylate, ε-caprolactone modified tris-(2-acryloxyethyl) isocyanurate, pentaerythritol triacrylate, trimethylolpropane triacrylate, ditrimethylolpropane trimethacrylate, ethoxylated glycerin triacrylate, ethoxylated pentaerythritol tetraacrylate, ditrimethylolpropane trimethacrylate Pantaerythritol tetraacrylate, dipentaerythritol hexaacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, 2,2 bis [4- (methacryloxyethoxy) phenyl] propane, tricyclodecane dimethanol dimethacrylate, 1,10-decanediol dimethacrylate, 1,6-hexanediol methacrylate, 1,9-nonanediol methacrylate, neopentyl glycol methacrylate, glycerin dimethacrylate, trimethylolpropane trimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polypropylene glycol diacrylate, polytetramethylene glycol diacrylate, glycerin triacrylate ethoxylate, dipentaerythritol polyacrylate, ethoxylated polypropylene glycol dimethacrylate, polypropylene dimethacrylate, and the like.

[0080] In addition, the polyfunctional acrylate may be a urethane (meth)acrylate oligomer (polymer) having two or more ethylenically unsaturated groups. For example, it may be phenyl glycidyl ether acrylate hexamethylene diisocyanate urethane prepolymer, phenyl glycidyl ether acrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, oligourethane acrylate, carboxylic acid-containing urethane acrylate oligomer, etc.

[0081] In addition, examples of polyfunctional acrylates include epoxy (meth)acrylate oligomers (polymers) having two or more ethylenically unsaturated groups, such as cresol novolac type epoxy acrylates and carboxylic anhydride modified epoxy acrylates.

[0082] In the present invention, a specific example of a preferred polyfunctional acrylate is one in which the functional group equivalent of the ethylenically unsaturated group is 200 g / eq or less. This allows a primer layer with high durability to be obtained. The functional group equivalent of the ethylenically unsaturated group is preferably 150 g / eq or less, more preferably 27 g / eq or more and 150 g / eq or less. This allows a primer layer with higher durability to be obtained. Here, the functional group equivalent represents the molecular weight of a compound per functional group. That is, it is a value obtained by dividing the molecular weight of the polyfunctional acrylate by the number of ethylenically unsaturated groups. Specifically, it is a value obtained by dividing the molecular weight of the polyfunctional acrylate, which is a (meth)acrylate monomer (oligomer), a urethane modified product thereof, a urethane (meth)acrylate monomer (oligomer), and an epoxy modified product thereof, an epoxy (meth)acrylate monomer (oligomer), by the number of (meth)acryloyl groups, which are ethylenically unsaturated groups. Examples of compounds satisfying such functional group equivalents include pentaerythritol tetraacrylate (88 g / eq), dipentaerythritol tetraacrylate (105 g / eq), dipentaerythritol hexaacrylate (96 g / eq), trimethylolpropane triacrylate (99 g / eq), trimethylolpropane tetraacrylate (117 g / eq), 1,3,5-tris(2,2-diacryloyloxymethyl-3-(2,2,2-triacryloyloxymethylethoxy)propylhexylcarbamate)isocyanurate (153 g / eq), and ethoxylated dipentaerythritol hexaacrylate (185 g / eq).

[0083] Among these, those having six or more functional groups in one molecule are particularly preferred in order to further enhance the durability of the coating layer, and examples thereof include dipentaerythritol hexaacrylate (6 functional), ethoxylated dipentaerythritol hexaacrylate (6 functional), and 1,3,5-tris(2,2-diacryloyloxymethyl-3-(2,2,2-triacryloyloxymethylethoxy)propylhexylcarbamate)isocyanurate (15 functional).

[0084] <Multifunctional vinyl compounds> As a monomer constituting the polyvinyl copolymer, a multifunctional vinyl compound can be suitably used. In the present invention, the multifunctional vinyl compound means a monomer having at least two ethylenically unsaturated groups in the molecule. Specific examples of the multifunctional vinyl compound include diallyl ether, diethylene glycol divinyl ether, 1,3-diallyloxy-2-propanol, 1,2,3-triallyloxy-2-propanol, 2,2 bisallyloxymethyl-1-propanol, 2,2 bisallyloxyethyl-1-butanol, 2,2 bisallyloxymethyl-1-hexanol, 3,3 bisallyloxyethyl-1-butanol, 3,3 bisallyloxyethyl-1-hexanol, 2, Examples of such alkyl ethers include 2,2-aryloxymethyl-1-ethanol, 2,2,2-aryloxymethyl-1-propanol, 2,2,2-aryloxymethyl-1-butanol, 2,2,2-aryloxymethyl-1-hexanol, 1,5-hexadiene-3,4-diol, diallyl isophthalate, 1,5-hexanediene, tetraallyloxyethane, tetraallyloxypropane, tetraallyloxybutane, triallyl citrate, and divinyl adipate.

[0085] Surfactants In the present invention, the composition for forming a coating layer can contain a surfactant that dissolves in 2-methoxyethanol at a weight concentration of 0.1% or more and has 9 or more carbon atoms in the hydrophobic part of the molecule. This allows the proportion of the compound having a betaine structure in the surface region of the coating layer to be sufficiently higher than the proportion in the interior of the coating layer or in the region on the substrate side, that is, the component containing the betaine structure can be arranged in a gradient in the surface region of the coating layer, preferably on the surface of the coating layer. The surfactant has a property of dissolving in 2-methoxyethanol at a weight concentration of 0.1% or more at 25°C, so that the surfactant is sufficiently dissolved in the composition for forming a coating layer and the compound having a betaine structure can be arranged in a gradient on the surface of the coating layer. Furthermore, the surfactant has a number of carbon atoms in the hydrophobic part of the molecule of 9 or more, so that the compound having a betaine structure can be uniformly distributed on the surface of the coating layer. The hydrophobic part of the surfactant can be, for example, any one of alkyl, alkene, aryl, and alkylene glycol except ethylene glycol, or a combination thereof.

[0086] In the present invention, the mechanism by which the composition for forming a coating layer contains a surfactant having 9 or more carbon atoms in the hydrophobic part of the molecule and the compound having a betaine structure does not aggregate and a member that is uniformly inclined arranged on the surface of the coating layer can be efficiently formed is thought to be as follows, but this is merely a hypothesis and the present invention is not limited in any way by this hypothesis. When the surfactant is dissolved in the composition for forming a coating layer, the surfactant forms reverse micelles or reverse vesicles in the solvent. Then, the compound having a betaine structure is enclosed in the reverse micelles or inside the reverse vesicles. After the reverse micelles or reverse vesicles rise to the surface during drying of the composition for forming a coating layer, they collapse on the surface, and the surfactant and the compound having a betaine structure remain on the surface. Here, when the number of carbon atoms in the hydrophobic part of the surfactant is small, they repel the compound containing two or more hydrophobic polymerizable functional groups, and the surfactants aggregate with each other, and the compound having a betaine structure is drawn into the aggregated part, resulting in the compound having a betaine structure aggregate. On the other hand, when the number of carbon atoms in the hydrophobic part of the surfactant is sufficiently large, there is no repulsion with the compound containing two or more hydrophobic polymerizable functional groups, and it spreads uniformly on the surface. At that time, it is considered that the compound having a betaine structure also spreads uniformly on the surface at the same time due to the interaction with the surfactant.

[0087] The surfactant preferably has a branched structure. A branched structure is one having a tertiary carbon in the hydrophobic portion, or one having a structure in which an atom other than hydrogen is bonded to a secondary carbon. By having a branched structure, the hydrophobic portion spreads spatially, so that reverse micelles or reverse vesicles are easily formed. This allows the compound having a betaine structure to be uniformly distributed on the surface of the coating layer.

[0088] Alternatively, in the present invention, the composition for forming the coating layer may contain a surfactant having a polymerizable functional group in the molecule. The mechanism by which a compound having a betaine structure does not aggregate and a member having a uniform inclination arrangement on the surface can be efficiently formed by using a composition containing a surfactant having a polymerizable functional group in the molecule is considered as follows, but it is merely a hypothesis, and the present invention is not limited by this hypothesis at all. A compound having a betaine structure, a compound containing two or more polymerizable functional groups in the molecule, and a surfactant having a polymerizable functional group in the molecule form reverse micelles or reverse vesicles in a solvent, and precipitate on the surface during drying of the solvent. When polymerized by ultraviolet light or the like after drying, if a surfactant without a polymerizable functional group is used, this surfactant will shrink because it does not polymerize with other compounds, and as a result, the compound having a betaine structure will aggregate, but in the present invention, a surfactant having a polymerizable functional group is used, and this surfactant will polymerize with other compounds and is less likely to shrink, so that the aggregation of the compound having a betaine structure can be suppressed.

[0089] In the present invention, the surfactant contained in the composition for forming a coating layer is preferably one that is soluble in 2-methoxyethanol at a weight concentration of 0.1% or more, contains a molecule having 9 or more carbon atoms in the hydrophobic part of the molecule, and further has a polymerizable functional group.

[0090] In the coating layer forming composition of the present invention, suitable examples of the surfactant include sulfosuccinic acid esters, dialkylammonium salts, trialkylammonium salts, sorbitan fatty acid esters, polyoxypropylene allyl ether phosphate esters, ammonium salts of esters of sulfuric acid and ethoxylated allylalkyl glyceryl ethers, polyoxyalkylene alkenyl ethers, sodium alkylaryl sulfosuccinates, polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ester ammonium salts, and the same amine salts.

[0091] Organic solvents In the present invention, the composition for forming a coating layer may contain an organic solvent. This can improve the wettability to the substrate or adjust the viscosity of the composition for forming a coating layer. As the organic solvent, alcohols such as methanol, ethanol, IPA (isopropanol), and n-butanol, cellosolves such as 2-methoxyethanol and methoxypropanol, ketones such as acetone, and DMF (N,N'-dimethylformamide) can be used, but are not limited thereto. In addition, a plurality of types of organic solvents may be mixed as necessary. Furthermore, water or the like may be mixed. The solvent can also be used when preparing the composition for forming a primer layer, which will be described later.

[0092] Polymerization initiator The coating layer-forming composition preferably contains a polymerization initiator. As the polymerization initiator, known ones can be used, for example, a photopolymerization initiator or a thermal polymerization initiator.

[0093] Preferred examples of the photopolymerization initiator include Irgacure 651, Irgacure 184, Irgacure 500, Irgacure 2959, Irgacure 127, Irgacure 907, Irgacure 369, Irgacure 1300, Irgacure 819, Irgacure 1800, Irgacure OXE01, Irgacure OXE02, Darocur 1173, Darocur TPO, Darocur 4265, etc., all of which are provided by BASF. Note that in some cases, the trade names of these photopolymerization initiators have been changed from "Irgacure" or "Darocur" to "Omnirad."

[0094] As a preferred example of the thermal polymerization initiator, a thermal radical generator such as a peroxide, a persulfate, or an azo compound is preferably used.

[0095] Non-ionic Monomers In the present invention, the coating layer forming composition can contain a nonionic monomer. This allows the coating layer obtained by curing the coating layer forming composition to contain a structure represented by formula (A2). In the present invention, the nonionic monomer means a monomer having one or more ethylenically unsaturated groups and an oxyalkylene in the molecule. The nonionic monomer is hydrophilic. The nonionic monomer is more preferably a monomer having a (meth)acrylic skeleton and an oxyalkylene group in the molecule.

[0096] In the present invention, the nonionic monomer may be a monofunctional nonionic monomer represented by the following formula (I1). [ka] In formula (I1), L2 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R2 is H or CH3; R 12 is H or CH3 or C2H5, Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; a is a natural number.

[0097] In the present invention, the nonionic monomer may be a bifunctional nonionic monomer having an oxyalkylene group, represented by the following formula (I2). [ka] In formula (I2), L2 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; a is a natural number.

[0098] In the present invention, the nonionic monomer may be a trifunctional nonionic monomer 1 having an oxyalkylene group, represented by the following formula (I3). [ka] In formula (I3), L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; Y is a linear or cyclic hydrocarbon group having 1 to 10 carbon atoms; b, c, and d are each independent natural numbers.

[0099] In the present invention, the nonionic monomer may be a trifunctional nonionic monomer 2 having an oxyalkylene group, represented by the following formula (I4). [ka] In formula (I4), L3 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R2 is H or CH3; Y is a linear or cyclic hydrocarbon group having 1 to 10 carbon atoms; b, c, and d are each independent natural numbers.

[0100] In the present invention, the nonionic monomer may be a tetrafunctional nonionic monomer having an oxyalkylene group, represented by the following formula (I5). [ka] In formula (I5), L1 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), L2 is -OCO-, -NHCO-, -(CH2) m - (where m is a natural number), R1 is H or CH3; Y is a linear or cyclic hydrocarbon group having 1 to 10 carbon atoms; b, c, d, and e are each independent natural numbers.

[0101] In the present invention, specific examples of nonionic monomers include 4-hydroxybutyl acrylate, 2-methoxyethyl acrylate (2-methoxyethyl acrylate), 2-[2-(2-methoxyethoxy)ethoxy]ethyl acrylate, 2-hydroxyethyl methacrylate (2-hydroxyethyl methacrylate (HEMA)), 2-methoxyethyl methacrylate, diethylene glycol monomethyl ether methacrylate, hydroxypropyl methacrylate, N-(hydroxymethyl)acrylamide, N-(2-hydroxyethyl)acrylamide, N-(methoxymethyl)acrylamide, N-(methoxymethyl)methacrylamide, N-(hydroxymethyl)methacrylamide, methoxydiethylene glycol methacrylate, ... Examples of the alkoxytetraethylene glycol methacrylate include methoxypolyethylene glycol methacrylate, methoxypolyethylene glycol acrylate, polyethylene glycol methacrylate, N-(4-hydroxyphenyl)methacrylamide, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, alkoxylated trimethylolpropane acrylate, alkoxylated trimethylolpropane methacrylate, alkoxylated glycerin acrylate, alkoxylated glycerin methacrylate, alkoxylated pentaerythritol tetraacrylate, and alkoxylated pentaerythritol tetramethacrylate. Among these, 2-hydroxyethyl methacrylate (HEMA), methoxytetraethylene glycol methacrylate, methoxypolyethylene glycol methacrylate, 2-methoxyethyl acrylate, and diethylene glycol dimethacrylate are preferred. More preferred are 2-hydroxyethyl methacrylate (HEMA) and methoxypolyethylene glycol methacrylate.

[0102] Anionic Monomers In the present invention, the composition for forming a coating layer can contain an anionic monomer. This allows the coating layer obtained by curing the composition for forming a coating layer to contain a structure represented by formula (A2). In the present invention, the anionic monomer means a compound having at least one anion and an ethylenically unsaturated group in the molecule. In the present invention, the anion is -COO - , -PO4 2- , -HPO4 - , -SO3 - Examples of anions include:

[0103] In the present invention, examples of the anionic monomer include anionic monomers represented by the following formulas (J1) and (J2). [ka] In formula (J1), L2 is -COO-, -CONH-, -(CH2) m -(m is a natural number), -Ph-, R2 is H or CH3; M1 is any one of a hydrogen ion, an ammonium ion, and an alkali metal ion. [ka] In formula (J2), L2 is -COO-, -CONH-, -(CH2) m -(m is a natural number), -Ph-, R2 is H or CH3; R 13 is an organic group containing C and H as essential components and O as an optional component, and not containing N or S, M1 is any one of a hydrogen ion, an ammonium ion, and an alkali metal ion.

[0104] In the present invention, specific examples of the anionic monomer include (meth)acryloyloxymethanesulfonic acid, potassium (meth)acryloyloxymethanesulfonate, sodium (meth)acryloyloxymethanesulfonate, 2-((meth)acryloyloxy)ethanesulfonic acid, potassium 2-((meth)acryloyloxy)ethanesulfonate, sodium 2-((meth)acryloyloxy)ethanesulfonate, 3-((meth)acryloyloxy)propane-1-sulfonic acid, potassium 3-((meth)acryloyloxy)propane-1-sulfonate, sodium 3-((meth)acryloyloxy)propane-1-sulfonate, 4-((meth)acryloyloxy)butane-1-sulfonic acid, potassium 4-((meth)acryloyloxy)butane-1-sulfonate, 4-((meth)acryloyloxy)butane-1-sulfonic acid, potassium 4-((meth)acryloyloxy)butane-1-sulfonate, 4-((meth)acryloyloxy)butane-1-sulfonic acid, ) acryloyloxy) butane-1-sulfonic acid sodium, 5-((meth)acryloyloxy) pentane-1-sulfonic acid, 5-((meth)acryloyloxy) pentane-1-sulfonic acid potassium, 5-((meth)acryloyloxy) pentane-1-sulfonic acid sodium, 6-((meth)acryloyloxy) hexane-1-sulfonic acid, 6-((meth)acryloyloxy) hexane-1-sulfonic acid potassium, 6-((meth)acryloyloxy) hexane-1-sulfonic acid sodium, 2-acrylamido-2-methylpropane sulfonic acid, 2-acrylamido-2-methylpropane sulfonic acid potassium, 2-acrylamido-2-methylpropane sulfonic acid sodium, styrene sulfonic acid, potassium styrene sulfonate, and sodium styrene sulfonate.

[0105] Cationic Monomers In the present invention, the composition for forming a coating layer can contain a cationic monomer. This allows the coating layer obtained by curing the composition for forming a coating layer to contain a structure represented by formula (A2). In the present invention, the cationic monomer means a compound having at least one or more cations and ethylenically unsaturated groups in the molecule. In the present invention, the cation can be a cation such as an ammonium ion. In the present invention, the cationic monomer can be a cationic monomer represented by the following formula (K). [ka] In formula (K), L2 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R2 is H or CH3; R 14 is -(CH2) l - (l is a natural number from 1 to 10), R 15 , R 16 , R 17 are each independently an organic group containing C and H as essential components and O as an optional component, and not containing N or S, M2 is any one of a hydroxide ion, a fluorine ion, a chloride ion, a bromide ion, and an iodine ion.

[0106] In the present invention, specific examples of the cationic monomer include 2-((meth)acryloyloxy)-N,N,N-trimethylethanaminium chloride, 2-((meth)acryloyloxy)-N,N,N-triethylethanaminium chloride, N-(2-(meth)acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride, (3-(meth)acrylamidopropyl)trimethylammonium chloride, and N-(2-(meth)acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride.

[0107] Primer layer In the present invention, when the substrate 1 is an inorganic material such as glass, ceramic, or metal, a primer layer 3 may be formed to strengthen the adhesion between the inorganic material and the coating layer 2. The primer layer 3 is preferably formed between the inorganic material (hereinafter referred to as the "inorganic substrate") that is the substrate 1 and the coating layer 2. In order to increase the adhesion, the primer layer 3 needs to bond to both the inorganic substrate and the coating layer 2. For this reason, the primer layer 3 is preferably a layer containing silicon atoms.

[0108] Primer layer forming composition The primer layer 3 is preferably a cured composition for forming a primer layer. The composition for forming a primer layer may contain a commonly used silane-based or phosphoric acid-based coupling agent. In addition, it is preferable that these coupling agents contain an ethylenically unsaturated group such as an acryloyl group or a methacryloyl group in order to further strengthen the adhesion with the coating layer.

[0109] <Silane compounds> Silane compound can be suitably used as silane coupling agent. In the present invention, silane compound means an organic compound having hydrolyzable Si-OR group (reactive silyl group, OR can be hydroxyl group or hydrolyzable group. Hydrolyzable group is, for example, alkoxy group, halogeno group. Specifically, -OCH3, -OCH2CH3, -Cl can be mentioned.). Specific examples of silane compounds include tetraethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, 3-methacryloxymethyltriethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxymethyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, Silane, 3-glycidoxypropyltriethoxysilane, p-styryltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-ureidopropyltrialkoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-trimethoxysilylpropylsuccinic anhydride, and the like.

[0110] In the present invention, a specific example of a preferred silane compound is a compound having three or more hydrolyzable Si-OR groups for adhering to an inorganic substrate and an acrylic or methacrylic polymerizable functional group for adhering to a coating layer that is an organic film. Examples of such silane compounds include 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, 3-methacryloxymethyltriethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-methacryloxymethyltrimethoxysilane.

[0111] <Phosphate compounds> As the phosphate coupling agent, a phosphate compound can be preferably used. In the present invention, the phosphate compound is a compound having a covalent bond P(OH) n It means an organic compound having a group (adsorbent phosphate group, n is any one of 1 to 3, and OH group may be its base substitute such as ONa, OK, ONH4, etc.). As the phosphate compound, those containing phosphoric acid or a phosphate as an adsorbent functional group and an acryl group, methacryl group, or vinyl group as a polymerizable functional group in the molecule are preferable. Specific examples include 2-acryloxyethyl phosphoric acid, 2-acryloxyethyl phosphoric acid, 2-methacryloxyethyl phosphoric acid, 2-methacryloxyethyl phosphoric acid, 2-acryloxypropyl phosphoric acid, 2-acryloxypropyl phosphoric acid, 2-methacryloxypropyl phosphoric acid, 2-methacryloxypropyl phosphoric acid, 2-methacryloxypropyl phosphoric acid, vinyl phosphoric acid, 2-acryloxybutyl phosphoric acid, 2-acryloxybutyl phosphoric acid, 2-methacryloxybutyl phosphoric acid, 2-methacryloxybutyl phosphoric acid, vinyl phosphoric acid, or their phosphates.

[0112] Optional ingredients Other optional components may be added to the coating layer and the primer layer, such as ultraviolet absorbers, light stabilizers, antioxidants, leveling agents, defoamers, thickeners, anti-settling agents, and various additives such as dyes, pigments, and matting agents that control the design properties of the paint, within a range that does not impair the stain resistance of the member.

[0113] Base material In the present invention, the substrate is not particularly limited. As the material of the substrate, any material generally used as a water-related component, such as resin, metal, inorganic material (glass, ceramic, etc.), can be used. In addition, the shape of the substrate can be a general shape of a water-related component. For example, it may be a flat plate or a complex shape.

[0114] Manufacturing method of components The member according to the present invention can be produced, for example, by the following method.

[0115] <Preparing the substrate> A substrate is prepared. In the present invention, it is preferable to pretreat the substrate. For example, it is preferable to wash the substrate with a neutral detergent and rinse with ion-exchanged water or ultrapure water. Any water droplets remaining on the substrate surface are preferably dried using an air blower or a dryer.

[0116] <Preparation of Coat Layer-Forming Composition> A compound having a betaine structure; a compound containing two or more polymerizable functional groups in the molecule, preferably a monomer capable of forming a polyacrylic or polyvinyl copolymer; a surfactant that dissolves in 2-methoxyethanol at a weight concentration of 0.1% or more and has 9 or more carbon atoms in the hydrophobic part in the molecule or has a polymerizable functional group; a polymerization initiator; and other components are mixed in any ratio and dissolved in a solvent. The solution is stirred to obtain a composition for forming a coating layer. The weight concentration of the compound having a betaine structure is preferably 0.1% to 10%, and the weight concentration of the monomer capable of forming a polyacrylic or polyvinyl copolymer is preferably 1% to 90%.

[0117] <Application of Coating Layer-Forming Composition> The composition for forming a coating layer is applied onto the substrate. A known method may be used as the coating method. For example, the composition may be applied by a general method such as brush coating, spray coating, dip coating, spin coating, curtain coating, or bar coating. The coating amount can be adjusted according to these coating conditions to adjust the film thickness of the resulting cured product. In the present invention, the film thickness of the formed coating layer is preferably in the range of 0.1 μm to 200 μm. This allows the effect of suppressing protein adhesion to be sufficiently obtained, and further allows abrasion resistance to be expressed. The film thickness of the coating layer is more preferably in the range of 1 to 100 μm, and even more preferably in the range of 1 to 20 μm.

[0118] <Drying> The coating layer forming composition applied on the substrate is dried. In the present invention, when the coating layer forming composition contains an organic solvent (organic solvent), it is preferable to dry the coating layer forming composition after applying it on the substrate in order to remove the organic solvent. In addition, in consideration of the productivity of the member, drying by heating can be preferably used. The fact that the solvent has been sufficiently removed can be confirmed by, for example, whether the coating layer forming composition drips when the substrate is tilted.

[0119] <Curing> The coating layer forming composition applied on the substrate is cured. Examples of the curing means include heat curing, active energy ray curing, and a combination of heat curing and active energy ray curing. When heat curing is performed, a known thermal polymerization initiator can be used as the polymerization initiator, and a known method of heating with infrared rays or hot air can be used. In addition, in the case of active energy ray curing, examples of the radiation include visible light of 400 to 800 nm, ultraviolet light of 400 nm or less, and electron beams. Usually, relatively inexpensive ultraviolet light or visible light is preferably used rather than electron beams, which require expensive equipment. When active energy ray curing is performed using ultraviolet light or visible light, a known photopolymerization initiator can be used. When ultraviolet light is used, examples of the ultraviolet light generating source include low pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, xenon lamps, gallium lamps, metal halide lamps, ultraviolet lasers, and ultraviolet light such as sunlight. The irradiation atmosphere may be air or an inert gas such as nitrogen or argon.

[0120] <Formation of primer layer> In the present invention, when the substrate 1 is an inorganic material such as glass, pottery, or metal, a primer layer 3 may be formed on the inorganic substrate before forming the coating layer 2 on the inorganic substrate. This can further strengthen the adhesion between the inorganic substrate and the coating layer 2. The composition for forming a primer layer can be prepared, for example, by dissolving the above-mentioned coupling agent and a solvent, and, if necessary, a catalyst for promoting the hydrolysis reaction in an arbitrary weight ratio, and stirring the mixture. Thereafter, the prepared composition for forming a primer layer can be applied to the inorganic substrate and dried to form the primer layer 3.

[0121] Purpose The member according to the present invention can be suitably used as an antifouling material, an antifogging material, a quick-drying material, an antistatic material, a biocompatible material, and the like. For example, it can be applied to general members used in wet areas. Examples of wet areas include bathrooms, toilets, washrooms, and kitchens. Specific examples of wet area members for bathrooms include floors, bathtubs, walls, ceilings, counters, aprons, drains, mirrors, and the like. For toilets, toilet bowls, tanks, toilet lids, toilet seats, and warm water washing toilet seats, and the like. For washrooms, wash basins, wash basin counters, mirrors, lighting, plumbing fixtures, drains, cabinets, washing machine pans, and the like. For kitchens, sinks, counters, plumbing fixtures, drains, dishwashers, dish dryers, cooking ranges, kitchen hoods, and ventilation fans, and the like. EXAMPLES

[0122] The present invention will be described in more detail with reference to the following examples, although the present invention is not limited to these examples.

[0123] 1. Preparation 1-1. Base material The following substrates were prepared: Acrylic plate: Acrylite EX (manufactured by Mitsubishi Rayon Co., Ltd.), colorless transparent plate, thickness 2 mm

[0124] 1-2.Reagents The following reagents were prepared:

[0125] <Multifunctional acrylate> Dipentaerythritol polyacrylate

[0126] <Polymerization initiator> A mixture of 1-hydroxycyclohexyl phenyl ketone and benzophenone in a weight ratio of 1:1 (BASF Irgacure 500)

[0127] <Organic solvent> 2-Methoxyethanol

[0128] <Compounds with betaine structure> Betaine Monomer 1: 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid Betaine monomer 2: 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl phosphate

[0129] <Anionic Monomer> Anionic Monomer 1: Sodium 2-acrylamido-2-methylpropanesulfonate

[0130] <Surfactant> Surfactant Reagent 1: Sodium Alkylaryl Sulfosuccinate The standard content was 40% by weight. Surfactant Reagent 2: Polyoxypropylene allyl ether phosphate ester The standard content was 97-99% by weight. Surfactant Reagent 3: Ammonium salt of sulfuric acid and ethoxylated aryl alkyl glyceryl ether ester The standard content was 99% or more by weight. Surfactant Reagent 4: Ammonium polyoxyalkylene alkenyl ether sulfate The standard content was 19-21% by weight. Surfactant Reagent 5: Sodium dioctyl sulfosuccinate (Aerosol OT) The standard content was 75% or more by weight. Surfactant Reagent 6: Sorbitan Monolaurate The standard content was 99% or more by weight. Surfactant Reagent 7:1-Sodium Hexanesulfonate The standard content was 99% or more by weight. Surfactant Reagent 8: Sodium monododecyl phosphate The standard content was 75% or more by weight.

[0131] Among surfactant reagents 1 to 8, only surfactant reagent 7 is a surfactant having less than 9 carbon atoms in the hydrophobic part of the molecule, and only surfactant reagent 8 is a surfactant having a solubility in 2-methoxyethanol of less than 0.1.

[0132] 2. Preparation of component samples Examples 1 to 7 <Pretreatment> The surface of the acrylic plate, which was the substrate, was washed with a neutral detergent and rinsed with ultrapure water. Water droplets were blown off from the surface of the substrate with an air blower, and the substrate was dried in a dryer at 60°C for 30 minutes.

[0133] <Preparation of Coat Layer-Forming Composition> Betaine monomer 1 or 2 as a compound having a betaine structure was dissolved in an organic solvent at 1% by weight, polyfunctional acrylate at 30%, polymerization initiator at 0.75%, and surfactant reagents 1 to 8 as a surfactant at the weight concentrations shown in Table 1. The mixture was then stirred with a stirrer for 1 hour to prepare a composition for forming a coat layer. As described above, the weight concentrations of the surfactants shown in Table 1 are the concentrations of the surfactant reagents contained in each composition for forming a coat layer. For example, the weight concentration of sodium alkylaryl sulfosuccinate contained in reagent 1 is 40%, so the concentration of the surfactant (sodium alkylaryl sulfosuccinate) itself contained in the composition is 0.12% (0.3×40 / 100) by weight. The concentrations of other surfactants are calculated in the same manner. <Formation of coating layer> The prepared composition for forming a coating layer was applied with a bar coater (#24). Immediately after application, the substrate was placed in a hot air drying oven and left to stand at 60°C for 10 minutes. Thereafter, the substrate was irradiated with an ultraviolet ray irradiation device (MDB15001N-01, manufactured by Sun Energy Co., Ltd.) with an integrated light dose of 1000 mJ / cm 2 The applied surface was irradiated with UV light to cure so that the viscosity reached 100 ppm (measured using an ultraviolet integrating light meter, C9536-254, manufactured by Hamamatsu Photonics K.K.).

[0134] To remove the unhardened components, after washing with a neutral detergent, it was rinsed with ultrapure water, left standing at room temperature for 1 hour or more to dry, and a member sample was obtained.

[0135] Example 8 In the production method of Example 2, member samples were obtained in the same manner except that the betaine monomer 1 was changed to 0.5% and 0.5% of anionic monomer 1 was added, each by weight concentration.

[0136] Comparative Example 1 In the production method of Example 1, member samples were obtained in the same manner except that a surfactant was not included in the composition for forming the coating layer.

[0137] Comparative Examples 2 and 3 In the production method of Example 1, member samples were obtained in the same manner except that surfactant reagents 7 and 8 were added at the weight concentrations shown in Table 1 instead of surfactant reagent 1 (0.3 wt%) in the composition for forming the coating layer.

[0138] 3. Evaluation and Results 3-1.XPS evaluation <Preparation of Evaluation Samples> A region with a size of about 1 cm square was cut from the plate-shaped member sample and used as a measurement sample. Before measurement, the surface of the measurement sample was washed to sufficiently remove the dirt adhering to the surface. Specifically, it was slid and washed with a sponge using a neutral detergent, then ultrasonically washed in ultrapure water at room temperature for 10 minutes, and then thoroughly rinsed with ultrapure water.

[0139] <XPS Measurement> ·XPS Measurement Device K-alpha (manufactured by ThermoFisher Scientific Co., Ltd.) was used. ·XPS Measurement Conditions X-ray Conditions: Monochromatized AlKα ray, 72W - 12KV Photoelectron Extraction Angle: 90° Analysis Region: 400μmφ Neutralization Gun Conditions: 200μA Ion gun condition: 10 mA (Survey) Time per step: 10 ms Energy step size: 1.000 eV Sweep: 2 times Pass energy: 200 eV Scanning range: -10 to 1350 eV (Narrow) Time per step: 50 ms Energy step size: 0.100 eV Sweep: 5 times Pass energy: 50 eV Scanning range: C1s peak 279.000 eV to 298.000 eV, O1s peak 525.000 eV to 545.000 eV, N1s peak 392.000 eV to 410.000 eV, S2p peak 157.000 eV to 175.000 eV, Si2p peak 95.000 eV to 110.000 eV, P2p peak 124.000 eV to 144.000 eV

[0140] <Calculation of atomic concentrations of each atom (S, N)> The atomic concentrations of the detected elements were calculated from the obtained spectra using the data analysis software Thermo Avantage (version 5.9916, manufactured by Thermo Fisher Scientific Co., Ltd.). First, using the spectra obtained from the survey analysis, it was confirmed whether the cleaning was properly performed. Next, for the spectra obtained from the narrow analysis, the charge correction was performed with the C1s peak set to 284.5 eV. After that, the background was removed by the Smart method for the peaks based on the electron orbits of each measured atom, and then the peak area intensity was calculated. An analysis process of dividing by the device-specific sensitivity coefficient preset in the data analysis software was performed to calculate the atomic concentrations when the total of C atoms, O atoms, N atoms, S atoms, and P atoms was 100%.

[0141] <Peak separation of N atoms> The +1-valent N atom (N) contained in the betaine structure +) and the peaks from other zero-valent N atoms (N 0 To separate the peaks from N + The peak position was fixed at 401.4 to 401.8 eV and the full width at half maximum of the peak was fixed at 1.6 eV. 0 The peak position of N was fixed at 398.7 to 399.4 eV and peak fitting was performed. + , N 0 The atomic concentration of each was calculated.

[0142] The following conditions were used for peak fitting: <Peak fitting conditions> Fitting Algorithm:Powell Maximum Iterations:90 Convergence:1e-05 Gauss-Lorentz Mix:Product

[0143] S atom concentration and N atom concentration of the example and comparative example samples + The atomic concentrations and P atomic concentrations are shown in Table 1.

[0144] In addition, the analysis depth by XPS is approximately 10 nm, but in the manufacturing method of the component samples of the examples and comparative examples, a sufficient amount of composition is applied and cured to form a layer thickness of 10 nm, and the layer thickness is sufficiently thicker than the analysis depth by XPS. Therefore, the analysis by XPS can analyze the surface components of the coating layer without being affected by the substrate. In addition, the coated surface can be covered by the application of the bar coat, and the substrate is not exposed. As described above, the analysis by XPS can analyze the surface components of the coating layer without being affected by the substrate.

[0145] GCIB-XPS evaluation <Preparing evaluation samples> The measurement sample was a 1 cm square area cut from a plate-shaped component sample. Before the measurement, the surface of the measurement sample was cleaned to thoroughly remove any dirt adhering to the surface. Specifically, the sample was rubbed with a sponge using a neutral detergent, then ultrasonically cleaned in ultrapure water at room temperature for 10 minutes, and then thoroughly rinsed with ultrapure water. ·XPS measurement device The XPS measurement device used was QUANTERA II (manufactured by ULVAC-PHI, Inc.). XPS measurement conditions X-ray conditions: Monochromatic AlKα radiation, 25W-15KV Photoelectron extraction angle: 45° Analysis area: 100μmφ Neutralizer gun requirements: Auto Neutralizer Ion gun conditions: Auto Neutralizer Time per step: 50 ms Energy step size: 0.100 eV Sweep: 5 times Pass energy: 55 eV Scan range: C1s peak 279.000eV~299.000eV, O1s peak 525.000eV~545.000eV, N1s peak 392.000eV~410.000eV, S2p peak 157.000eV~177.000eV, P2p peak 124.000eV~144.000eV GCIB sputtering conditions The following conditions were used for GCIB sputtering: Beam voltage: 10kV Beam current: 30nA

[0146] <Calculation of each atomic concentration (S, N)> The atomic concentrations of the detected elements were calculated from the obtained spectra using data analysis software MultiPaK (version 9.0, manufactured by ULVAC-PHI, Inc.). For the spectra obtained by narrow analysis, the C1s peak was charge-corrected with 284.5 eV. Then, after removing the background by the Shirley method for the peaks based on the electron orbits of each measured atom, the peak area intensity was calculated, and an analysis process of dividing by the sensitivity coefficient specific to the apparatus preset in the data analysis software was performed to calculate the atomic concentrations when the total of C atoms, O atoms, N atoms, S atoms, and P atoms was 100%.

[0147] <Separation of N atom peaks> For separating the peak derived from the +1 valence N atom (N + ) contained in the betaine structure and the peak derived from the other 0 valence N atom (N 0 ), the following method was used. The peak position of N + was fixed at 401.4 - 401.8 eV and the full width at half maximum of the peak was fixed at 1.6 eV, and the peak position of N 0 was fixed at 398.7 - 399.4 eV, and peak fitting was performed. From the results of the peak fitting, the atomic concentrations of N + and N 0 were calculated respectively.

[0148] When the surface of the coating layer was set as the film thickness depth 0 point and the interface between the coating layer and the substrate was set as the film thickness depth 1 point, for the N + atoms and S atoms of the sample of the example and the comparative example, the atomic concentrations at the surface (film thickness depth 0 point), the atomic concentrations at the film thickness depth 1 / 10 point, and the ratios of the atomic concentrations at the film thickness depth 1 / 10 point to the atomic concentrations at the surface were shown in Table 1 respectively.

[0149] The sputter rate was calculated by dividing the measured depth obtained by observing the sputter mark of the sample after measurement with a laser microscope by the sputter time. Also, by integrating the sputter time and the sputter rate, the depth at that time was calculated.

[0150] 3-3.Contact angle Using the following device and software, the static contact angle of water with respect to the surface of the coating layer was measured under the following measurement conditions. The results are shown in Table 1. Device: DMo-702 (manufactured by Kyowa Interface Science Co., Ltd.) Software: Interface Measurement / Analysis Integrated System FAMAS Version: 7.3.0 Measurement method: Droplet method Droplet volume: 2.0 μL Waiting time: 1000 ms Analysis method: θ / 2 method

[0151] 3-4. Haze Using the following device, the haze of the member was measured. It was determined that aggregation was present on the surface of the member with a haze value of 6.0 or more. Device: Haze Guard i (manufactured by BYK-Chemie) Measurement item: Transmission haze value

[0152] 3-5.SEM-EDX evaluation <Preparation of evaluation sample> A region with a size of about 1 cm square was cut from the plate-shaped member sample and used as the measurement sample. Before measurement, the surface of the measurement sample was washed to sufficiently remove the dirt adhering to the surface. An osmium coating was applied to the surface to impart conductivity. <SEM-EDX measurement> · SEM-EDX measurement device SEM measurement device: Regulus8220 (Hitachi High-Technologies Corporation) EDX measurement device: XFlash5060FlatQUAD (Bruker Corporation) was used. · SEM-EDX measurement conditions Acceleration voltage: 6 kV Irradiation current: 10 μA Condenser lens 1: 8 Magnification: 250 times · EDX analysis element: S

[0153] <Quantification of the number density of aggregation> Identification of the aggregates on the surface of the structure represented by formula (A1) and, in some cases, the structure represented by formula (A2) in the coating layer, and calculation and counting of the circle-equivalent diameter of the aggregates were performed using S distribution images obtained by SEM-EDX measurement and the image analysis library "OpenCV (version: 4.5.5)". Image analysis was performed according to the following procedure. The number density of aggregates having a circle-equivalent diameter of 4 μm for each sample is shown in Table 1. Image loading: The S distribution image obtained by SEM-EDX measurement was loaded. The image size of the S distribution image obtained by SEM-EDX measurement was 960px vertical and 1280px horizontal. The corresponding actual size was 384μm vertical and 512μm horizontal. -Cropping of the analysis part: The analysis part was cropped so that the display part of the scale bar, measurement conditions, etc. was not included in the analysis part. The image size after cropping was 760px vertically and 1280px horizontally. -Monochrome processing: The image was converted to monochrome. Gaussian blur processing: The kernel size was set to 3px vertically and 3px horizontally. · Binarization process: The threshold was set to the 90th percentile of the pixel values ​​of the entire image. Opening process: Opening process was performed to remove noise. The kernel size was set to 3px vertical and 3px horizontal. Closing process: Closing process was performed to fill holes in the foreground region. The kernel size was set to 3px vertical and 3px horizontal. The images after the closing process in Example 3 and Comparative Example 2 are shown in Figures 2 and 3, respectively. Extraction of connected regions: Connected regions were extracted and grouped into aggregates. Calculation of the equivalent circle diameter: The area of ​​the aggregate ( S ) to the equivalent circle diameter ( R ) was calculated.

number

[0154] 3-6. Protein adsorption evaluation <Preparation of protein-containing suspension> To 100 mL of ion-exchanged water, 1.0 g of BSA (bovine serum albumin (FV), pH 5.2, Nacalai Tesque, Inc.) was added as a protein, and the mixture was mixed with a stirrer for 1 hour to obtain a suspension.

[0155] <Protein adhesion and cleaning> The component sample was immersed in the above suspension for 5 minutes, and then removed from the suspension. The component sample was then dried in a thermostatic chamber at 40°C for 10 minutes. Then, ultrapure water was applied to the surface of the component sample using a dropper at a concentration of 0.4 [mL / cm 2 This procedure was repeated three times to obtain a component sample with BSA attached.

[0156] <Protein recovery and sample solution preparation> The BSA was wiped off from the component sample with a nonwoven fabric. The nonwoven fabric from which the BSA had been wiped off was placed in a 20 mL headspace vial (As One Corporation), 2 mL of 6 mol / L hydrochloric acid was added, and the material was left to stand at 110°C for 20 hours to carry out hydrolysis. The material was then dried on a hot plate at 120°C for 3 hours, and 2 mL of ultrapure water was added to dissolve the amino acid to obtain a component sample solution. In addition, BSA previously weighed in the same manner was hydrolyzed to obtain a calibration curve sample solution.

[0157] <High performance liquid chromatography (HPLC) measurement> HPLC measurement equipment Nexera Post-column Amino Acid Analysis System (Shimadzu Corporation) HPLC measurement conditions Column: Shim-pak amino-Na (Shimadzu Corporation) Ammonia trap column: ISC-30Na (Shimadzu Corporation) Mobile phase: Three-liquid gradient amino acid mobile phase kit Na type (Shimadzu Corporation) Flow rate: 0.6ml.min Reaction reagent: Amino acid analysis kit OPA reagent (Shimadzu Corporation) Flow rate: 0.2ml / min Detector: RF-10AXL (Shimadzu Corporation) Excitation wavelength 350 nm, emission wavelength 450 nm ·BSA quantitative method The component sample solution and the calibration curve sample solution were subjected to HPLC measurement, and the sum of the peaks in the obtained chromatogram was regarded as the peak area value. The amount of BSA in the component sample solution was calculated based on the calibration curve created from the calibration curve sample. This amount of BSA was regarded as the amount of protein adsorbed in the component sample.

[0158] 3-7. Evaluation of sliding durability A sliding durability test was carried out on the member sample of Example 3 using a sliding machine (manufactured by Tester Sangyo Co., Ltd.). A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) was soaked in a mixture of water and neutral detergent (Bath Magiclean, manufactured by Kao Corporation) in a weight ratio of 90:10, and subjected to a load of 25 [g / cm 2 The surface of the sample was reciprocated 5,000 times with the same cloth. The sample was washed with running water, dried, and the static contact angle of water was measured by the method described above. The sliding durability was evaluated according to the following criteria. ○: The static contact angle of water after the sliding test is 35 degrees or less ×: The static contact angle of water after the sliding test is greater than 35 degrees.

[0159] As a result, the static contact angle of water after the sliding durability test in the member sample of Example 3 was 20.5 degrees, and the evaluation was good.

[0160] 3-8. Film thickness evaluation The member sample of Example 3 was cut in the cross-sectional direction. The thickness of the coating layer on the cut portion was measured using a scanning electron microscope, and was found to be 10 μm. The scanning electron microscope used was as follows. Equipment: Regulus8220 (Hitachi High-Tech Corporation) Acceleration voltage: 1kV Magnification: 6000x

[0161] [Table 1] [Explanation of symbols]

[0162] 10. Materials 1 Base material 2 Coating Layer 3 Primer layer

Claims

1. A member including a substrate and a coating layer, The surface of the coating layer has the following formula (A1): 【Chemistry 1】 The aggregates having a circle equivalent diameter of 4 μm or more and containing the structure represented by 2 Contains 100 or less per In formula (A1), L 1 is -COO-, -CONH-, -(CH 2 ) m - (where m is a natural number), R 1 is H or CH 3 and X 1 is a functional group represented by the following formula (B1) or the following formula (B2), 【Chemistry 2】 【Chemistry 3】 In formula (B1), R 3 and R 6 Each independently represents -(CH 2 ) l - (l is a natural number from 1 to 10), R 4 and R 5 each independently represents an organic group containing C and H as essential components and O as an optional component, and not containing N or S, In formula (B2), R 7 and R 8 Each independently represents -(CH 2 ) l - (l is a natural number from 1 to 10), R 9 , R 10 , R 11 are each independently an organic group containing C and H as essential components and O as an optional component, and not containing N or S. A member characterized in that

2. When the surface of the coating layer is defined as a film thickness depth 0 point and the interface between the coating layer and the substrate is defined as a film thickness depth 1 point, the N + The ratio of the abundance (S) of the structure represented by formula (A1) using the concentration of N atoms or S atoms as an index, at a point 1 / 10 of the film thickness depth, obtained by GCIB-XPS measurement. + 2. The member according to claim 1, wherein the ratio (B / S) of the abundance ratio (B) of the structure represented by formula (A1), which is expressed by the concentration of S atoms or S atoms as an index, is 0 or more and less than 1.

3. 3. The member according to claim 1, wherein the contact angle of water with respect to the surface of the coating layer is 35° or less.

4. Either or both of a compound represented by the following formula (H1) and a compound represented by the following formula (H2): 【Chemistry 4】 (In formula (H1), L 1 is -COO-, -CONH-, -(CH 2 ) m-(m is a natural number), R 1 is H or CH 3 and R 3 and R 6 Each independently represents -(CH 2 ) l - (l is a natural number from 1 to 10), R 4 and R 5 are each independently an organic group containing C and H as essential components and O as an optional component, and not containing N or S. 【Chemistry 5】 (In formula (H2), L 1 is -COO-, -CONH-, -(CH 2 ) m-(m is a natural number), R 1 is H or CH 3 and R 7 and R 8 Each independently represents -(CH 2 ) l - (l is a natural number from 1 to 10), R 9 , R 10 , R 11 are each independently an organic group containing C and H as essential components and O as an optional component, and not containing N or S); A compound containing two or more polymerizable functional groups in the molecule. surfactants, and Organic solvents Including, The surfactant is soluble in 2-methoxyethanol at a weight concentration of 0.1% or more, and has a hydrophobic part having 9 or more carbon atoms in its molecule, or has a polymerizable functional group in its molecule.

5. One or more compounds selected from the group consisting of the following formulae (I1) to (I5), (J1), (J2) and (K): 【Chemistry 6】 (In formula (I1), L 2 is -COO-, -CONH-, -(CH 2 ) m - (where m is a natural number), R 2 is H or CH 3 and R 12 is H or CH 3 Or C 2 H 5 and Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; a is a natural number.) 【Chemistry 7】 (In formula (I2), L 2 is -COO-, -CONH-, -(CH 2 ) m - (where m is a natural number), L 3 is -OCO-, -NHCO-, -(CH 2 ) m - (where m is a natural number), R 2 is H or CH 3 and Y is a linear, branched or cyclic hydrocarbon group having 1 to 10 carbon atoms; a is a natural number.) 【Chemistry 8】 (In formula (I3), L 3 is -OCO-, -NHCO-, -(CH 2 ) m - (where m is a natural number), R 2 is H or CH 3 and Y is a linear or cyclic hydrocarbon group having 1 to 10 carbon atoms; b, c, and d are each independent natural numbers.) 【Chemistry 9】 (In formula (I4), L 3 is -OCO-, -NHCO-, -(CH 2 ) m - (where m is a natural number), R 2 is H or CH 3 and Y is a linear or cyclic hydrocarbon group having 1 to 10 carbon atoms; b, c, and d are each independent natural numbers.) 【Chemistry 10】 (In the following formula (I5), L 1 is -COO-, -CONH-, -(CH 2 ) m - (where m is a natural number), L 2 is -OCO-, -NHCO-, -(CH 2 ) m - (where m is a natural number), R 1 is H or CH 3 and Y is a linear or cyclic hydrocarbon group having 1 to 10 carbon atoms, and b, c, d, and e are each independently a natural number. 【Chemistry 11】 (In formula (J1), L 2 is -COO-, -CONH-, -(CH 2 ) m -, -Ph- (where m is a natural number), R 2 is H or CH 3 (It is) 【Chemistry 12】 (In formula (J2), L 2 is -COO-, -CONH-, -(CH 2 ) m -, -Ph- (where m is a natural number), R 2 is H or CH 3 and R 13 is an organic group containing C and H as essential components, O as an optional component, and not containing N or S. 【Chemistry 13】 (In formula (K), L 2 is -COO-, -CONH-, -(CH 2 ) m - (where m is a natural number), R 2 is H or CH 3 and R 14 is -(CH 2 ) l - (l is a natural number from 1 to 10), R 15 , R 16 , R 17 each independently represents an organic group containing C and H as essential components and O as an optional component, and not containing N or S, M 2 is either a hydroxide ion, a fluorine ion, a chloride ion, a bromide ion, or an iodine ion.) The composition of claim 4 further comprising:

6. 1. A method for manufacturing a component, comprising: Applying the composition according to claim 4 or 5 to a substrate; removing the organic solvent from the composition applied to the substrate; and polymerizing the composition from which the organic solvent has been removed.

Citation Information

Patent Citations

  • Hydrophilic resin and medical material

    JP1998152533A

  • Composition for hydrophilic cured product

    WO2015087810A1

  • Hydrophilic structure and production method for hydrophilic structure

    WO2018155577A1